(untitled) (Bangladesh Journal of Medical Science, 2019)
The prime purpose of the study was to assess the quality of life of physically disabled adults attending at rehabilitation center in Dhaka city, Bangladesh and to determine the relationship of the type of disability, educational level and relationship with the family with quality of life.Participants were 500 adults with physical disabilities. Thestructured questionnaire consist of WHOQOL-BREF were used as research instruments. When dividing the participants into three groups according to the level of total QOL score, in physical domain majority (96.2%) had fair level QOL score. In psychological domain veryfew(5.4%) had poor level and more than half (53.2%) had fair level QOL score and rest of them had good QOL score (41.4%). more than one third (37.2%) and nearly half(47.0%) had fair and good level respectively whereas rest of them (15.8%) had poor level of QOL in Social domain. In environmental domain a minimum number(3.8%) had poor QOL score but almost half (43.6%) and more than half (52.6%) had fair and good level of QOL score. The Cronbach’s alpha coefficient of WHOQOL-BREF was adequate (0.914) for all 26 questions and for each domain the values are: Physical health domain (0.812), Psychological health domain (0.831), Social relationship domain (0.68) and Environmental health domain (0.78). Statistically significant correlations present between all domains. Mean and percentage of satisfaction rating in DOM1, DOM2 and DOM3 and DOM4 was higher in males than females. There were significant differences found in WHOQOL-BREF score between different education level group, different marital statusgroup,different employment statusgroup, differentincome level group, relationship with family, utilization of primary rehabilitation in four domains and total of WHOQOL-BREF (P < 0.05). multiple linear regression observed that education level and utilization of primary rehabilitation center is most important factor that affects QOL of study population in total and four domains of WHOQOL.The findings from this study confirm that the WHOQOL-BREF questionnaire is a reliable instrument to measure quality of life in disable adults. From the data, it appears that Bangladeshi disable adults have WHOQOL-BREF scores that might be considered to indicate a fair level of quality of life. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.607-614